Integrated design and optimization of technologies for utilizing low grade heat in process industries - Kwak, Dong-Hun; Binns, Michael; Kim, Jin-Kuk (Applied energy, 2014)
The utilization of low grade heat in process industries has significant potential for improving site-wide energy efficiency. This paper focuses on the techno-economic analysis of key technologies for energy recovery and re-use, namely: Organic Rankine Cycles (ORC), boiler feed water heating, heat pumping and absorption refrigeration in the context of process integration. Process modeling and optimization in a holistic manner identifies the optimal integrated configuration of these technologies, with rigorous assessment of costs and technical feasibility of these technologies. For the systematic screening and evaluation of design options, detailed process simulator models are evaluated and optimization proceeds subject to design constraints for the particular economic scenarios where technology using low grade heat is introduced into the process site. Case studies are presented to illustrate how the proposed modeling and optimization framework can be useful and effective in practice, in terms of providing design guidelines and conceptual insights for the application of technologies using low grade heat. From the case study, the best options during winter are the ORC giving a 6.4% cost reduction for the ideal case with low grade heat available at a fixed temperature and boiler feed water heating giving a 2.5% cost reduction for the realistic case with low grade heat available at a range of temperatures. Similarly during summer boiler feed water heating was found to be the best option giving a 3.1% reduction of costs considering a realistic waste heat temperature profile.